Dynamic synaptic modification threshold: computational model of experience-dependent plasticity in adult rat barrel cortex. - Benusková, L (1994)
Previous electrophysiological experiments have documented the response of neurons in the adult rat somatic sensory ("barrel") cortex to whisker movement after normal experience and after periods of experience with all but two whiskers trimmed close to the face (whisker "pairing"). To better understand how the barrel cortex adapts to changes in the flow of sensory activity, we have developed a computational model of a single representative barrel cell based on the Bienenstock, Cooper, and Munro (BCM) theory of synaptic plasticity. The hallmark of the BCM theory is the dynamic synaptic modification threshold, theta M, which dictates whether a neuron's activity at any given instant will lead to strengthening or weakening of the synapses impinging on it. The threshold theta M is proportional to the neuron's activity averaged over some recent past. Whisker pairing was simulated by setting input activities of the cell to the noise level, except for two inputs that represented untrimmed whiskers. Initially low levels of cell activity, resulting from whisker trimming, led to low values for theta M. As certain synaptic weights potentiated, due to the activity of the paired inputs, the values of theta M increased and after some time their mean reached an asymptotic value. This saturation of theta M led to the depression of some inputs that were originally potentiated. The changes in cell response generated by the model replicated those observed in in vivo experiments. Previously, the BCM theory has explained salient features of developmental experience-dependent plasticity in kitten visual cortex. Our results suggest that the idea of a dynamic synaptic modification threshold, theta M, is general enough to explain plasticity in different species, in different sensory systems, and at different stages of brain maturity.